2017
DOI: 10.1016/j.kjms.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological evaluation of Marjolin ulcers over two decades

Abstract: Malignant changes arising on the previously traumatized or chronically inflamed skin are defined as Marjolin ulcers. They can develop on many different lesions but frequently they are detected on burn scars. Histopathologically, Marjolin ulcers are mostly diagnosed as squamous cell carcinoma and they need special attention when especially located on the lower extremities. In this study, 63 patients treated for Marjolin ulcers between January 2000 and March 2015 were evaluated according to etiology, histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 30 publications
1
29
1
1
Order By: Relevance
“…As like other studies, the most common site of MU in our study was lower limb. The second most common site in our study was upper limb which is in contradiction to other studies in which head and neck is the most common site after lower limb [9][10][11]. In our study regional lymphadenopathy was found in 16% cases by combining clinical examination with routine USG evaluation of regional LN basin.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…As like other studies, the most common site of MU in our study was lower limb. The second most common site in our study was upper limb which is in contradiction to other studies in which head and neck is the most common site after lower limb [9][10][11]. In our study regional lymphadenopathy was found in 16% cases by combining clinical examination with routine USG evaluation of regional LN basin.…”
Section: Discussioncontrasting
confidence: 97%
“…Although we did therapeutic LN dissection in 15 cases for cases which had LN metastasis confirmed on preoperative evaluation, none of our patients underwent any form of prophylactic LN surgery and none had any recurrence in regional LNs during the follow up. Recurrences are not uncommon and an incidence of 14-33% been reported in literature [11,14]. 19.1% patients in our study developed local recurrence.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…2,5) Marjolin's ulcer most commonly refers to a squamous cell carcinoma, 3) and burns are considered the most common cause of this condition. 1,2) A case of Marjolin's ulcer in a patient with a diabetic foot has been reported, but it occurred 60 years after a scar was formed.…”
Section: Discussionmentioning
confidence: 99%
“…The average latent period of the chronic type was reported about more than 30 years. 2,5) Here, we present a case of Marjolin's ulcer that developed from early stage untreated diabetic foot ulcer.…”
mentioning
confidence: 99%